Can Treatment With Citicoline Eyedrops Reduce Progression in Glaucoma? The Results of a Randomized Placebo-controlled Clinical Trial - Rossetti, Luca (J Glaucoma, 2020)
PRECIS: Citicoline eyedrops in patients with progressing glaucoma. PURPOSE: This study aimed to test whether the additional therapy with citicoline eyedrops to intraocular pressure (IOP)-lowering treatment could slow glaucoma progression in patients with worsening of damage and IOP 18 mm Hg or less. DESIGN: This was a randomized, double-masked, placebo-controlled, multicenter 3-year study. OUTCOMES: The outcomes studied were difference in the visual field (mean deviation, MD, of 24-2; MD of 10-2) rates of progression and difference in retinal nerve fiber layer (RNFL) thickness change between the 2 study groups at 3 years. METHODS: Patients with mild to moderate open-angle glaucoma (OAG) showing damage progression of at least −0.5 dB/y in the 2 years before enrollment despite IOP ≤18 mm Hg were randomized to receive citicoline eyedrops or placebo 3 times daily for 3 years. Patients were followed every 3 months and underwent a visual field examination with 24-2 and 10-2 strategies and RNFL assessment. Analysis of variance and linear models were used to test the differences between groups. RESULTS: Eighty patients were randomized in the trial. The mean 3-year rates of progression were −1.03 (2.14) dB in the citicoline group and −1.92 (2.23) dB in the placebo group (P=0.07) for 24-2 MD and −0.41 (3.45) dB in the citicoline group and −2.22 (3.63) dB in the placebo group (P=0.02) for 10-2 MD. On average, patients receiving citicoline eyedrops lost 1.86 μm of RNFL in 3 years, versus 2.99 μm in the placebo group (P=0.02). CONCLUSIONS: Additional treatment with citicoline eyedrops to IOP-lowering treatment might reduce disease progression in patients with progressing glaucoma despite IOP ≤18 mm Hg.